Optical and Electrical properties of organic Aluminum phthalocyanine based thin films for organic electronics. - Benhaliliba, Mostefa (University of Thi-Qar Journal of Science, 2024)
Thought this research, the optical and electrical properties of organic aluminum phthalocyanine (AlPc) molecule based thin film are emphasized. The transmittance of such materials presents a narrow peak  and valley within a range of 446 nm. Dielectric parameters like refractive and extinction coefficient are studied within Uv-vis-IR range. Optical band gap and Urbach energy are determined found to be 2.6  eV and 33 meV. Based on single oscillator, dispersion energy and related parameters like E0, Ed, S0, l0, n0, epsil,